1,1′,1′′,1′′′-(Oxydimethanetriyl)tetrakis(4-fluorobenzene) - K. R. Roopashree; H. D. Kavitha; K. S. Katagi; O. Kotresh; H. C. Devarajegowda (Acta Crystallographica Section E, 2014)
In the title compound, C26H18F4O2, the dihedral angles between pairs of benzene rings linked to the same C atom are 80.55 (8) and 79.11 (7)°. The crystal packing features C—H...π interactions and shows stacking when viewed along the c axis.